2013
DOI: 10.7852/ijie.2013.27.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Structure of the Bumblebee, Bombus ignitus (Hymenoptera: Apidae), Based on Mitochondrial COI Gene and Nuclear Ribosomal ITS2 Sequences

Abstract: The bumblebee, Bombus ignitus (Hymenoptera: Apidae), is a valuable natural resource that is widely utilized for greenhouse pollination in South Korea. Understanding the magnitude of genetic diversity and geographic relationships is of fundamental importance for long term preservation and utilization. As a first step, we sequenced a partial COI gene of mitochondrial DNA (mtDNA) corresponding to the "DNA barcode" region and the complete internal transcribed spacer 2 (ITS2) of nuclear ribosomal DNA from 88 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(36 reference statements)
0
7
1
Order By: Relevance
“…Although Oh et al . () examined four local populations (CC, JS, TB and MJ) that overlapped with the present study, the results are inconsistent with our findings that the five populations examined here (CC, JS, SB, TB and MJ) are significantly genetically divergent based on nine microsatellite loci. This disagreement most likely results from the fact that microsatellites evolve faster and have more polymorphisms than nuclear non‐coding regions of the ITS2 , thereby accumulating enhanced levels of mutations (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Although Oh et al . () examined four local populations (CC, JS, TB and MJ) that overlapped with the present study, the results are inconsistent with our findings that the five populations examined here (CC, JS, SB, TB and MJ) are significantly genetically divergent based on nine microsatellite loci. This disagreement most likely results from the fact that microsatellites evolve faster and have more polymorphisms than nuclear non‐coding regions of the ITS2 , thereby accumulating enhanced levels of mutations (i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…The nuclear ITS2 data obtained from the nine local populations in South Korea revealed that these populations are all genetically indistinguishable, suggesting high levels of gene flow among them, regardless of geographic distance among those populations (Oh et al . ). Although Oh et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations